(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In present work new series of 7-chloro-4-aminoquinoline analogs were designed to discover chemically diverse antimalarial leads. The widely used computational tool molecular docking is applied to study molecular recognition, which aims to predict analogs’ binding mode and binding affinity to the active site. The potential binding of the selected analogs to the Plasmodium falciparum lactate dehydrogenase enzyme (PfLDH) active site was analyzed using SYBYL X2.0 software running on a core-2 duo Intel processor workstation. Compounds F5, F9 and F1 showed highest binding affinity in term of total scores 9.50, 7.86 and 7.01, respectively. Analogs with the best dock score were synthesized and evaluated for antimalarial potential against chloroquine sensitive RKL-2 strain. Compounds F5, F28 and F9 showed good antimalarial activity in term of MIC50 value 0.35, 0.45 and 0.56 μg/mL, respectively. Further optimization and exploration of 7-chloro-4-aminoquinoline lead could be useful to identify novel, antimalarial molecules.